2021
DOI: 10.3389/fphys.2021.805509
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzymes and Heat-Shock Protein Genes of Green Peach Aphid (Myzus persicae) Under Short-Time Heat Stress

Abstract: The management of insect pests under fluctuating temperatures has become an interesting area of study due to their ability to stimulate defense mechanisms against heat stress. Therefore, understanding insect’s physiological and molecular response to heat stress is of paramount importance for pest management. Aphids are ectothermic organisms capable of surviving in different climatic conditions. This study aimed to determine the effects of short-time heat stress on green peach aphid Myzus persicae under control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…In the present study, the CAT activities of male and female P. pseudoannulata in all treatment groups were significantly higher than that of the control group. This was consistent with the changing trend of CAT for Myzus persicae and H. graminicola [ 29 , 65 ]. This indicated that CAT is the main pathway for the breakdown of H 2 O 2 in P. pseudoannulata , so they need to maintain relatively high activity under heat stress at different times and temperatures.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, the CAT activities of male and female P. pseudoannulata in all treatment groups were significantly higher than that of the control group. This was consistent with the changing trend of CAT for Myzus persicae and H. graminicola [ 29 , 65 ]. This indicated that CAT is the main pathway for the breakdown of H 2 O 2 in P. pseudoannulata , so they need to maintain relatively high activity under heat stress at different times and temperatures.…”
Section: Discussionsupporting
confidence: 86%
“…To cope with this damage, heat stressed arthropods reduce cell damage through antioxidant enzyme [ 7 , 26 ]. The main antioxidant enzymes in arthropods are superoxide dismutase (SOD), catalase (CAT), and glutathione transferase (GST) [ 26 , 27 , 28 , 29 , 30 ]. The function of SOD is to degrade superoxide anions (O 2− ) to hydrogen peroxide (H 2 O 2 ) and oxygen (O 2 ), following which CAT decomposes H 2 O 2 to H 2 O and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to plant allelochemicals, temperature can generate ROS and cause oxidative stress in aphid tissues. Khursid et al [ 69 ] showed that heat stress significantly increased the H 2 O 2 and MDA content in M. persicae .…”
Section: Discussionmentioning
confidence: 99%
“…Durak et al [ 74 ] and Dampc et al [ 75 ] showed that an increase in temperature caused alterations in SOD and CAT activity, which were highest at 28 °C, in Aphis pomi (De Geer), Macrosiphum rosae (L.) and Cinara cupressi (Buckton). Khursid et al [ 69 ] stated that SOD and CAT activity in M. persicae adults increased under short-term heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…These primers were used in the analysis of the RT-qPCR data. The actin gene of aphid was used as an internal control ( Khurshid et al, 2021 ). The relative expression level was quantified using the comparative 2 −ΔΔCt method ( Livak and Schmittgen, 2001 ).…”
Section: Methodsmentioning
confidence: 99%